2023
DOI: 10.3389/fphar.2022.1007654
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of probiotics in Parkinson’s constipation: A systematic review and meta-analysis

Abstract: Background: Parkinson’s disease (PD) is the most common neurodegenerative disease closely related to the immune system, among whose prodromes constipation is a representative symptom. Recent Randomized Controlled Trials (RCTs) have proved that probiotics can be used to effectively treat PD constipation, but the results are inconsistent. We performed a meta-analysis to assess the efficacy and safety of probiotic therapy on Parkinson’s constipation.Methods: Questions about the research focus were constructed bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 86 publications
0
10
0
Order By: Relevance
“…A recent meta-analysis of 9 such studies as well as 3 single-arm studies (n=818 patients) revealed that oral probiotics resulted in improved stool frequency [odds ratio: 3.22, 95% CI (1.97, 5.29)] while decreasing the number of laxatives needed [mean difference: −0.72, 95% CI (−1.04, −0.41)] 91 . Motor function, notably, was also improved per the UPSDRS-III score [mean difference: −6.58, 95% CI (−12.02, 1.14)].…”
Section: Constipationmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent meta-analysis of 9 such studies as well as 3 single-arm studies (n=818 patients) revealed that oral probiotics resulted in improved stool frequency [odds ratio: 3.22, 95% CI (1.97, 5.29)] while decreasing the number of laxatives needed [mean difference: −0.72, 95% CI (−1.04, −0.41)] 91 . Motor function, notably, was also improved per the UPSDRS-III score [mean difference: −6.58, 95% CI (−12.02, 1.14)].…”
Section: Constipationmentioning
confidence: 99%
“…A recent meta-analysis of 9 such studies as well as 3 single-arm studies (n = 818 patients) revealed that oral probiotics resulted in improved stool frequency [odds ratio: 3.22, 95% CI (1.97, 5.29)] while decreasing the number of laxatives needed [mean difference: −0.72, 95% CI (−1.04, −0.41)]. 91 Motor function, notably, was also improved per the UPSDRS-III score [mean difference: −6.58, 95% CI (−12.02, 1.14)]. Trials of both single-strain and multi-strain probiotic formulations were included, with individual trials that demonstrated benefits ranging from those that studied only Lactobacillus strains to combinations of Lactobacillus, Bifidobacterium, and Bacillus.…”
Section: Probioticsmentioning
confidence: 99%
“…The long-term safety of microbiota-targeted therapies in PD has yet to be thoroughly evaluated. While preliminary studies regarding the impact of probiotics on GI and motor symptoms have rendered promising results [62][63][64], longterm efficacy and safety studies [65], levodopa interaction risk evaluations [15], as well as therapeutic dose identification [62,66] are necessary. In comparison, FMT studies are more heterogeneous methodologically despite the limited data available on PD models [44]; some short-term studies attest to its effectiveness in treating gastrointestinal dysfunction and improving motor symptoms [45,46,67,68].…”
Section: Clinical Translation Of Rodent Studies On Microbiota-targete...mentioning
confidence: 99%
“…74 Probiotics, overall, appear to increase stool frequency and improve stool consistency in PD-related constipation, though which precise formulation is optimal and exactly how these effects are mediated remain to be determined. 75 Reference has already been made to the uncertainty surrounding the impact of dopaminergic medications on bowel function in PD. One short-term study in a small number of patients provided some evidence to indicate that the potent dopaminergic agent, apomorphine, may improve anorectal and pelvic floor coordination and promote evacuation.…”
Section: Management Of Bowel Dysfunction In Pdmentioning
confidence: 99%
“…74 Probiotics, overall, appear to increase stool frequency and improve stool consistency in PD-related constipation, though which precise formulation is optimal and exactly how these effects are mediated remain to be determined. 75…”
Section: Bowel Dysfunction In Pdmentioning
confidence: 99%